Engineering Pt in ceria for a maximum metal-support interaction in catalysis - Yeung, C; Yu, K; Fu, Q; Thompsett, D; Petch, M; Tsang, S (2005)
Conventional supported metal catalysts are metal nanoparticles deposited on high surface area oxide supports with a poorly defined metal-support interface. Typically, the traditionally prepared Pt/ceria catalyzes both methanation (H2/CO to CH4) and water-gas shift (CO/H2O to CO2/H2) reactions. By using simple nanochemistry techniques, we show for the first time that Pt or PtAu metal can be created inside each CeO2 particle with tailored dimensions. The encapsulated metal is shown to interact with the thin CeO2 overlayer in each single particle in an optimum geometry to create a unique interface, giving high activity and excellent selectivity for the water-gas shift reaction, but is totally inert for methanation. Thus, this work clearly demonstrates the significance of nanoengineering of a single catalyst particle by a bottom-up construction approach in modern catalyst design which could enable exploitation of catalyst site differentiation, leading to new catalytic properties. Copyright © 2005 American Chemical Society.